Self-Assessment System in Indonesian Taxation: Weakness or Strength? - Muhammad Ilman Iriawan Fitdra; Inayati Inayati (Department of Public Administration, 2022)
This study describes the challenges of compliance in the formation of tax morality. This study examines the literature on self-assessment and tax compliance. This study explores a scientific review of tax compliance based on the application of a self-assessment system (SAS). All relevant data that is combined into information is revealed in this study by ensuring all components that need to be clarified about self-assessment and its implications for tax compliance. The conclusion of the study shows that in Indonesia, SAS is a tax system that requires a high level of tax compliance. The high and low levels of tax compliance can be caused by tax knowledge and system complexity.